1981
DOI: 10.1002/jbm.820150104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roughness on the thrombogenicity of a plastic

Abstract: Tubings extruded from one batch of polyvinylchloride resin at five temperatures ranging from 110 to 205 degrees C were tested for thrombogenicity in the saphenous vein and aorta of sheep. There was more thrombus in both the vein and aorta on tubings extruded at lower temperatures. The surface areas of renal infarction were smaller when lower temperature tubings were inserted into the aorta. Scanning electron microscopy showed that lower extrusion temperatures caused greater roughness on the tubings. This great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Our findings with electrospun fibers thus agree with conclusion derived from utilizing other types of surface topographies: it has been widely observed that platelet adhesion and blood reaction both depend on surface roughness [48][49][50][51][52], and that platelet adhesion and blood activation are also affected by other defined surface topographies, i.e. pillars [53], lenses [54] and struts [55].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings with electrospun fibers thus agree with conclusion derived from utilizing other types of surface topographies: it has been widely observed that platelet adhesion and blood reaction both depend on surface roughness [48][49][50][51][52], and that platelet adhesion and blood activation are also affected by other defined surface topographies, i.e. pillars [53], lenses [54] and struts [55].…”
Section: Discussionsupporting
confidence: 91%
“…We chose the more common and very exact contact method, because the disadvantage of a potential scratch on metallic surfaces is negligible. The profilometer method is widely applied in the microelectronics and metallurgy industries [17] and occasionally is used in biomaterials research [9,18,19]. The surface profile can be separated into ,~, 20"t:n ness and roughness is essentially one of scale.…”
Section: Discussionmentioning
confidence: 99%
“…The slope of the extinction at 405-nm wavelength versus time was normalized to the sample size to quantify the relative amount of adsorbed protein on Hydroxylation of the glass surface was performed by treatthe surfaces which is accessible for immune complex formaing precleaned microscopy slides with a mixture of 75% tion. The largest errors of the ELISA test are due to nonspesulfuric acid (100%) and 25% hydrogenperoxide (32%), cific interaction of the applied antibody with the substrate (piranha solution), at 100ЊC for 2 h. 3 After excessive rinsing or adsorbed proteins. Therefore, we always measured the with distilled water, the hydroxylated slides (Hydro) were corresponding nonspecific adsorption of antibodies on the stored in distilled water until usage or further treatments.…”
Section: Poly[bis(trifluoroethoxy)phosphazene]mentioning
confidence: 99%